Relationship Attitudes, Role of Parents, and The Community Environment With Knowledge About HIV/AIDS in Adolescent Class XI In SMK Muhammadiyah Serang - partono siswosuharjo; Nur Avenzoar (JOURNAL EDUCATIONAL OF NURSING(JEN), 2020)
Cases of STIs (Sexually Transmitted Infections) and HIV / AIDS are quite common among adolescents. Various types of STIs and HIV / AIDS are very influential on a person's health level in general and reproductive health conditions in particular because in general, various STI and HIV / AIDS infections are directly related to the human reproductive system. Even HIV / AIDS can have an impact on death. The purpose of this study was to determine the factors related to knowledge about HIV/AIDS in XI grade adolescents at SMK Muhammadiyah Serang in 2019. This research is an analytical survey research in which the research will be conducted using a cross sectional research method (cross-sectional). because in this study the independent and dependent variables will be observed at the same time. Based on the results of the study, it can be concluded that the distribution of adolescent knowledge about HIV / AIDS at SMK Muhammadiyah Serang in 2019 was poor as many as 56 respondents (59.8%) and good as many as 37 respondents (40.2%). The distribution of adolescent knowledge about HIV / AIDS based on the sex of women was 47 respondents (51.1%) and male respondents were 45 respondents (48.9%), based on the role of parents as many as 60 respondents (65.2%) and those who played a role 32 respondents (34.8%), based on the attitudes of students who have negative attitudes as many as 45 respondents (48.9%) and positive ones as many as 47 respondents (51.1%), based on the living environment as many as 24 respondents (26.1 %) and those who supported 68 respondents (73.9%), based on information technology as many as 30 respondents (32.6%) and 62 respondents (67.4%) who used it.